Penilaian Kelayakan Air Sebagai Sumber Air Bersih dan Air Minum Berdasarkan Water Quality Index (WQI) - Titra Hayyu Al Ghaitsi; Harnani Harnani (Mataram University, 2025)
Water is an important resource for human life and activities. The decline in water quality due to domestic activities, agriculture, and the existence of landfills has become an environmental problem that need serious attention. This study aims to assess water quality in Palemraya Village, Ogan ilir Regency, using the Water Quality Index (WQI) method with a Weighted Arithmetic Index approach. Samples were taken at four points representing surface water and groundwater sources. Physical, chemical, and biological parameters were tested in the laboratory in accordance with Permenkes No. 2 of 2023 standards. The results showed that the WQI values ranged from 8,96 to 83,11. Location S1, which is close to the landfill, had very poor water quality, while location P2 showed good water quality that could still be used after simple treatment. The main factors causing the decline in water quality were low pH and microbiological contamination due to domestic activities and leachate seepage. This study is expected to serve as a basis for efforts to manage sustainable clean water sources for the local community